UPAYA PENINGKATAN KINERJA PEGAWAI DI SATUAN POLISI PAMONG PRAJA DAERAH ISTIMEWA YOGYAKARTA - Hartana, Edhy; Hamid, Muda Setia (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This study aims to identify indicators that do not match reality with standards, to analyze the factors causing employee performance in the Civil Service Police Unit of the Special Region of Yogyakarta to formulate efforts to improve employee performance in the Civil Service Police Unit of the Special Region of Yogyakarta. In this study the authors used a descriptive research type with a qualitative research approach. To analyze how the condition of employee performance is used descriptive qualitative analysis. To find out why employee performance is still low, qualitative descriptive analysis is used. To analyze efforts to improve employee performance used qualitative analysis. The results of the study show that the performance of the Civil Service Police Unit for the Special Region of Yogyakarta is in the good category but is still not optimal, this can be seen from the fact that there are still employees who commit violations. The factors causing the decline in the performance of the Civil Service Police Unit for the Special Region of Yogyakarta are efforts to develop themselves that have not been maximized; Prioritizing office tasks over personal interests is still low; Compliance with regulations is still low; Time to go to work is not right. Efforts to improve the performance of the Civil Service Police Unit for the Special Region of Yogyakarta are providing motivation such as giving rewards and punishments; Giving Skills such as providing skills in the form of technical and non-technical; Giving Compensation such as personnel who are given awards for their work which is considered good; Position Promotions such as giving positions, promotions; Increasing and fostering legal awareness and legal compliance.